Deposits of Sorted Material in the Inarijoki-Tana River Valley in Lapland - Mansikkaniemi,Hannu (1970)
The paper deals with the morphology of the main valley of the drainage area and with the formations in the sorted material at the bottom of the valley. The sinuosity of the river valley is described by a method which facilitates and focuses on comparison of different river valleys. The depth and width of the valley is also systematically analysed. The melting of the continental ice sheet has been very rapid in the area. A late glacial sea phase has reached deep to the main valley. At the bottom of the valley there is a bed of sorted material, 20--70m thick. The most important formations are eskers, deltas, kame terraces, basin floor deposits, valley trains, outwash fans, river terraces and dunes. Their morphology and structure are explained in the paper. (Author) Revision of report dated 6 Nov 70.